Multimodal Glioma Image Segmentation Using Dual Encoder Structure and Channel Spatial Attention Block - Su, Run; Liu, Jinhuai; Zhang, Deyun; Cheng, Chuandong; Ye, Mingquan (Frontiers in Neuroscience, 2020)
Multimodal medical images provide signiﬁcant amounts of complementary semantic information. Therefore, multimodal medical imaging has been widely used in the segmentation of gliomas through computational neural networks. However, inputting images from different sources directly to the network does not achieve the best segmentation effect. This paper describes a convolutional neural network called F-S-Net that fuses the information from multimodal medical images and uses the semantic information contained within these images for glioma segmentation. The architecture of F-S-Net is formed by cascading two sub-networks. The ﬁrst sub-network projects the multimodal medical images into the same semantic space, which ensures they have the same semantic metric. The second sub-network uses a dual encoder structure (DES) and a channel spatial attention block (CSAB) to extract more detailed information and focus on the lesion area. DES and CSAB are integrated into U-Net architectures. A multimodal glioma dataset collected by Yijishan Hospital of Wannan Medical College is used to train and evaluate the network. F-S-Net is found to achieve a dice coefﬁcient of 0.9052 and Jaccard similarity of 0.8280, outperforming several previous segmentation methods.